2007
DOI: 10.1002/pbc.21435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of race on vincristine‐associated neurotoxicity in pediatric acute lymphoblastic leukemia patients

Abstract: The data support the hypothesis pharmacogenetic polymorphisms in CYP3A5 expression contribute to variability in vincristine metabolism and neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
84
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 13 publications
3
84
3
2
Order By: Relevance
“…90 The frequency of the risk allele was lower in individuals with African ancestry compared with the other ancestral groups, consistent with a lower incidence of vincristine neuropathy in African American patients. 91 A candidate-gene study found that variants in ABCB1, ACTG1, and CAPG were associated with vincristine neurotoxicity during ALL therapy, 92 although other candidate-gene studies found no associations with ABCB1 variants, despite its likely role in vincristine transport. 93,94 Although CYP3A5 affects vincristine metabolism, candidate-gene studies indicate that there are conflicting data on its association with neuropathy.…”
Section: Vincristinementioning
confidence: 99%
“…90 The frequency of the risk allele was lower in individuals with African ancestry compared with the other ancestral groups, consistent with a lower incidence of vincristine neuropathy in African American patients. 91 A candidate-gene study found that variants in ABCB1, ACTG1, and CAPG were associated with vincristine neurotoxicity during ALL therapy, 92 although other candidate-gene studies found no associations with ABCB1 variants, despite its likely role in vincristine transport. 93,94 Although CYP3A5 affects vincristine metabolism, candidate-gene studies indicate that there are conflicting data on its association with neuropathy.…”
Section: Vincristinementioning
confidence: 99%
“…Individuals who express CYP3A5 may metabolize vincristine more efficiently than nonexpressers, resulting in lower vincristine exposure and thus potentially less drug efficacy and toxicity. Clinical data demonstrate less vincristineinduced peripheral neuropathy in African Americans, and a recent retrospective study in children diagnosed with acute lymphoblastic leukemia and treated with vincristine revealed greater neuropathy in children with CYP3A5 low expresser genotypes (Renbarger et al, 2008;Egbelakin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in an ALL pediatric study, the mortality rates of African-American children with vincristine combination chemotherapy were 42% greater than those of Caucasian children after correcting for known prognostic factors such as compliance, clinical presentation, and tumor characteristics (Pollock et al, 2000). In addition, in a retrospective analysis with ALL patients, Caucasian children compared with African-American children were more likely to experience vincristine-associated neurotoxicity (Renbarger et al, 2008). Thus, interracial variability in vincristine exposure due to differences in metabolism may in part explain the differences in clinical outcomes between African-American and Caucasian children.…”
mentioning
confidence: 99%